Photosynthetic responses to temperature in tropical lotic macroalgae - Necchi Jr., Orlando [UNESP] (My University, 2004)
A comparative analysis of the photosynthetic responses to temperature (10-30°C) was carried out under short-term laboratory conditions by chlorophyll fluorescence and oxygen (O2) evolution. Ten lotic macroalgal species from southeastern Brazil (20°11-20°48′S, 49°18-49°41′W) were tested, including Bacillariophyta, Chlorophyta, Cyanophyta, Rhodophyta and Xanthophyta. Temperature had significant effects on electron transport rate (ETR) only for three species (Terpsinoe musica, Bacillariophyta; Cladophora glomerata, Chlorophyta; and C. coeruleus, Rhodophyta), with highest values at 25-30°C, whereas the remaining species had no significant responses. It also had similar effects on non-photochemical quenching and ETR. Differences in net photosynthesis/dark respiration ratios at distinct temperatures were found, with an increasing trend of respiration with higher temperatures. This implies in a decreasing balance between net primary production and temperature, representing more critical conditions toward higher temperatures for most species. In contrast, high net photosynthesis and photosynthesis/dark respiration ratios at high and wide ranges of temperature were found in three species of green algae, suggesting that these algae can be important primary producers in lotic ecosystems, particularly in tropical regions. Optimal photosynthetic rates were observed under similar environmental temperatures for five species (two rhodophytes, two chlorophytes and one diatom) considering both techniques, suggesting acclimation to their respective ambient temperatures. C. coeruleus was the only species with peaks of ETR and O 2 evolution under similar field-measured temperatures. All species kept values of ETR and net photosynthesis close to the optimum under a broad range of temperatures. Increased non-photochemical quenching, as a measure of thermal dissipation of excess energy, toward higher temperatures was observed in some species, as well as positive correlation of non-photochemical quenching with ETR, and were interpreted as two mechanisms of adaptation of the photosynthetic apparatus to temperature changes. Different optimal temperatures were found for individual species by each technique, generally under lower temperatures by O2 evolution, indicating dependence on distinct factors: increases in temperature generally induced higher ETR due to increased enzymatic activity, whereas increments of enzymatic activity were compensated by increased respiration and photorespiration leading to decreases in net photosynthesis.
Keywords: Chlorophyll fluorescence; Lotic; Macroalgae; Oxygen evolution; Photosynthesis; Temperature; macroalga; photosynthesis; primary production; temperature effect; algae; Bacillariophyta; Chlorophyta; Cladophora; Cladophora glomerata; Cyanobacteria; Eukaryota; Rhodophyta; Terpsinoe; Terpsinoe musica; Xanthophyceae